Optimization of a bio-based drilling fluid from waste Dacryodes Edulis (local pear) for oil exploration - Effiom, Precious-Chibuzo Oliver (Applied Engineering and Technology, 2023)
This study focused on the development and optimization of a bio-based drilling fluid from local pear seed for oil exploration, which can help lessen the environmental impact of oil spills. Local pear seed being a biodegradable material was collected, prepared, its oil extracted, modified and optimized to obtain an eco-friendly and cost-effective drilling fluid. The selected materials used for this study was Local pear oil. The drilling fluid was characterized for proximate parameters and ultimate parameters. The prepared drilling fluid was optimized using response surface methodology (RSM) provided by Design-Expert software 13.0. Central composite design (CCD) was applied to study the variables affecting rheology of drilling fluid. The process factors which include pH (A), viscosity (B), mud density (c), temperature (D), rheology (E) interacted to produce the response (drilling fluid yield) for the studied sample. The optimized drilling fluid yield and the optimum values were obtained through iterations of one hundred (100) solutions and the best yield was selected at iteration number seven (95th solution), at a pH of 1, Viscosity of 119.783cP, mud density of 10.473kg/L, Temperature of 100°C, and Rheology of 76.809s-1, and the optimized drilling fluid yield value was 91.144%. The acidity and the alkalinity of the drilling fluid were measured by the concentration of the 9.5 ion in the fluid. Therefore, the biomaterial studied has demonstrated its optimal effectiveness and potential application as an additive for the development of drilling fluid for oil exploration.